Process evaluation of a randomised controlled trial of a pharmacological strategy to improve hypertension control: protocol for a qualitative study. Issue 8 (17th August 2018) - Salam, Abdul; Webster, Ruth; Patel, Anushka; Godamunne, Pavithra; Pathmeswaran, Arunasalam; de Silva, H Asita; Rogers, Anthony; Jan, Stephen; Laba, Tracey-Lea
Abstract : Introduction: Globally, the prevalence of uncontrolled hypertension is high, particularly in low- and middle-income countries. There is a critical need for strategies to improve hypertension control. The early use of a fixed low-dose combination of three antihypertensive drugs (triple pill) has the potential to significantly improve hypertension control. The TRI ple Pill vs. U sual care M anagement for P atients with mild-to- moderate H ypertension (TRIUMPH) randomised controlled trial (RCT) is designed to test the effects of this strategy compared with usual care in patients with mild-to-moderate hypertension. This paper reports the protocol of a process evaluation of the TRIUMPH RCT. The objectives are to understand factors related to implementation of the intervention, mechanisms of effect, contextual factors that underpin the effectiveness of the triple pill strategy and the potential barriers and facilitators to implementing the strategy in clinical practice. Methods and analysis: Face-to-face semistructured in-depth interviews with a purposive sample of TRIUMPH RCT participants and healthcare professionals in Sri Lanka will be conducted. Healthcare professionals will include physicians and their staff who were involved in conducting the TRIUMPH RCT. Interviewees will be recruited sequentially until thematic saturation is achieved. Interviews will be audio recorded, transcribed verbatim and analysed in NVivo using framework analysis methods. Ethics and dissemination: The TRIUMPH RCT and process evaluation have received approval from the relevant Ethics Review Committee. All participants will be asked to provide written consent before participation. Findings from the study will be disseminated through publications and conference presentations. Trial registration number: ACTRN12612001120864, SLCTR/2015/020 ; Pre-results.